INDONESIA’S TAX AMNESTY LAW BASED ON THE PERSPECTIVE OF THE LAW AS AN ALLOCATIVE SYSTEM - Darmawan, Agus (Yustisia, 2016)
AbstractThis study aimed to evaluate academic on Law Number 11 of 2016 on the Tax Amnesty as the law as an allocative system approach as presented Lawrance M. Friedman. This study uses a normative approach. The results showed that the Law on Tax Amnesty academically has fulfilled the legal criteria for allocative as intended by Friedman. Tax Amnesty Program is the elimination of the tax owed should not sanction tax administration and criminal sanctions in the area of taxation by way of uncovering treasures and pay the ransom. Tax amnesty aimed to increase tax revenues in the State Budget, which is expected to be more sustainable State Budget to finance development programs for the welfare of all the people of Indonesia.